How intra-familial decision-making affects women’s access to, and use of maternal healthcare services in Ghana: a qualitative study - Ganle, John Kuumuori (BMC Pregnancy Childbirth, 2015)
BACKGROUND: There is some evidence to suggest that within the household, family and community settings, women in sub-Saharan Africa often have limited autonomy and control over their reproductive health decisions. However, there are few studies that examine how intra-familial decision-making power may affect women’s ability to access and use maternal health services. The purpose of this paper is to examine how intra-familial decision-making affects women’s ability to access and use maternal health services. METHODS: We conducted 12 focus group discussions and 81 individual interviews with a total of 185 expectant and lactating mothers in six communities in Ghana. In addition, 20 key informant interviews were completed with healthcare providers. Attride-Stirling’s thematic network analysis framework was used to analyse the data. RESULTS: Findings suggest that decision-making regarding access to and use of skilled maternal healthcare services is strongly influenced by the values and opinions of husbands, mothers-in-law, traditional birth attendants and other family and community members, more than those of individual childbearing women. In 49.2 %, 16.2 %, and 12.4 % of cases in which women said they were unable to access maternal health services during their last pregnancy, husbands, mothers-in-law, and husband plus mothers-in-law, respectively, made the decision. Women themselves were the final decision-makers in only 2.7 % of the cases. The findings highlight how the goal of improving access to maternal healthcare services can be undermined by women’s lack of decision-making autonomy through complex processes of gender inequality, economic marginalisation, communal decision-making and social power. CONCLUSION: Interventions to improve women’s use of maternity services should move beyond individual women to target different stakeholders at multiple levels, including husbands and mothers-in-law.